2009
DOI: 10.1055/s-0029-1185368
|View full text |Cite
|
Sign up to set email alerts
|

Editorial Gender Disparity in CABG Outcomes: An Independent Risk Factor or Not, Women Are at a Disadvantage

Abstract: In this issue of the Journal, Sharoni E. et al. from Rabin Medical Center evaluate the impact of female gender on postoperative morbidity and mortality after coronary artery bypass grafting (CABG) surgery. The authors retrospectively analyzed 1 758 isolated first-time CABG patients operated from 2003 to 2005 and found that women had distinctly different pre-and intraoperative profiles compared with men, and also a significantly higher postoperative mortality. On propensity scoring of 359 matched pairs, and val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Some authors believe that the observed differences in postoperative outcomes between males and females can be attributed to the varied distribution of the preoperative risk factors [5] and that some of these factors may even be more important predictors for postoperative mortality and morbidity than gender alone. [30][31][32] Furthermore, in agreement with our findings, several studies have noted an increased risk for postoperative morbidities in females, including prolonged mechanical ventilation, [13,14] surgical site infection, sepsis, [14] and renal complications; [8] however, not all studies have been able to confirm this risk. [5] In addition, our data did not always correspond to that found in other studies.…”
Section: Discussionsupporting
confidence: 90%
“…Some authors believe that the observed differences in postoperative outcomes between males and females can be attributed to the varied distribution of the preoperative risk factors [5] and that some of these factors may even be more important predictors for postoperative mortality and morbidity than gender alone. [30][31][32] Furthermore, in agreement with our findings, several studies have noted an increased risk for postoperative morbidities in females, including prolonged mechanical ventilation, [13,14] surgical site infection, sepsis, [14] and renal complications; [8] however, not all studies have been able to confirm this risk. [5] In addition, our data did not always correspond to that found in other studies.…”
Section: Discussionsupporting
confidence: 90%
“…Explanations for these observations are varied; however, the risk factors themselves may be more important than gender when assessing their impact on outcome data [31][32][33].…”
Section: Risk Factorsmentioning
confidence: 97%
“…2,4,5,18,19 Other factors that have been suggested to contribute to women's increased risk for operative mortality that may have played a role in our results include their smaller native coronary diameters, independent of body size, making revascularization more technically challenging, contributing to less complete revascularization and less frequent use of left internal mammary artery grafts 20À22 ; their more extensive microvascular dysfunction, which is less effectively addressed by CABG than the epicardial disease that predominates in men 20,23 ; and their more frequent need for postoperative inotropic support and periprocedural blood transfusions, and longer lengths of hospital stay, all of which influence morbidity and complications. 24 Regarding race, our results are consistent with those of studies ranging in setting from single centers to state and national databases, which have concluded that race or ethnicity itself is not a risk factor for operative CABG mortality, 9,11 but contradictory with those of 2 large studies (440,000 to 580,000 patients) that used national STS data from the mid-1990s and concluded that blacks and nonCaucasians had significantly higher risk-adjusted operative mortality than whites (odds ratio point estimates ranged from 1.16 to 1.29). 7,8 Possible explanations for the divergence in the results of these two large studies include not only the fact that the latter used substantially older data that might not reflect current patterns of care but also that, coming from a single center, our data are not subject to the differences in hospital quality that have been shown to explain as much as 35% of the disparity in mortality between races.…”
Section: Discussionmentioning
confidence: 97%